Do Managerial Objectives Drive Bad Acquisitions? - Mørck, Randall; Shleifer, Andrei; Vishny, Robert W. (Journal of Finance, 1990)
This paper documents for a sample of 327 US acquisitions between 1975 and 1987 three forces that systematically reduce the announcement day return of bidding firms. The returns to bidding shareholders are lower when their firm diversifies, when it buys a rapidly growing target , and when the performance of its managers has been poor before the acquisition. These results are consistent with the proposition that managerial rather than shareholders' objectives drive bad acquisitions.